2023
DOI: 10.1007/s12403-023-00586-5
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Exposure to Plastic Pollutants: Study of the Bisphenols and Perfluoroalkyls Effects on Human Stem Cell Models

Abstract: Endocrine disruptors (EDs), such as Bisphenols (BPs) and Perfluoroalkyls (PFs), are a class of plastic pollutants widely used in industrial applications. Human exposure to these molecules usually occurs through ingestion of contaminated food and water. Once entered the human body they can interfere with endogenous hormone signaling, leading to a wide spectrum of diseases. It has been reported that BPs and PFs can cross the placental barrier accumulating in the fetal serum, but the detrimental consequences for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Although association studies already suggested a relationship between the exposure to EDs and PD development, our results provide the first evidence of the threatening action of BPs and PFs on a human mDAN model, showing the neuronal biological features affected by EDs exposure. In line with previous data obtained in other neuronal or stem cell models [30][31][32], in our setting BPs and PFs did not impact cell viability. However, high content imaging analysis showed that 72-hour exposure to BPA, BPS, or PFOA determined an increase of αSyn levels in human mDANs and this effect was particularly evident at the highest concentration tested (2 µM) (Figure 2D, Figure 3B, Figure 6B).…”
Section: Discussionsupporting
confidence: 93%
“…Although association studies already suggested a relationship between the exposure to EDs and PD development, our results provide the first evidence of the threatening action of BPs and PFs on a human mDAN model, showing the neuronal biological features affected by EDs exposure. In line with previous data obtained in other neuronal or stem cell models [30][31][32], in our setting BPs and PFs did not impact cell viability. However, high content imaging analysis showed that 72-hour exposure to BPA, BPS, or PFOA determined an increase of αSyn levels in human mDANs and this effect was particularly evident at the highest concentration tested (2 µM) (Figure 2D, Figure 3B, Figure 6B).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, PFs have been shown to interfere with thyroid, androgenic, and estrogenic pathways in pregnancy, affecting placental morphology and fetal survival and growth [27][28][29][30]. We already described the sensibility of the diverse human stem cells to different doses of BPs and PFs [31,32]. In this study, the toxic effects of BPs and PFs, alone or in combination, were tested in hAFSCs and hFM-MSCs by evaluating cell proliferation, mitochondrial response, and the expression of genes pivotal for stem cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al investigated the effect of different PFs on cultured rat hippocampal neurons and demonstrated that PFOS and PFOA decreased neurite length by about 25% and 20%, respectively 51 . It is also known that BPs and PFs, interfering with the endocrine system, do not show a linear dose–response effect 36 , 37 . In our study we found that some investigated features were altered at low (0.1 µM) and high concentration (2 µM), but not at medium ones (1 µM).…”
Section: Discussionmentioning
confidence: 99%